The Legal Dilemma and Coping Path of Satellite Navigation Data Transaction - Chen, Long (International Journal of Social Sciences and Public Administration, 2024)
With the improvement of navigation technology, the navigation system has become an important spatial infrastructure in China. Navigation systems are also widespread in all aspects of our lives. Satellite navigation data has become an important driving force for Chinas economic development. The emergence of more and more satellite navigation data, but also increases the difficulty of satellite navigation data protection. Shanghai has proposed to establish a satellite data trading platform. However, the legal protection of satellite navigation data transaction still faces many obstacles. One is that the current legal system does not have clear provisions on the protection of satellite navigation data. Second, the restriction of commercial behavior and practice on open satellite navigation data. Therefore, through the analysis of Chinas current legislation, it is put forward the type protection of satellite navigation data, and to clarify the structure and responsibilities of the satellite navigation data.